PERAN GURU AGAMA ISLAM DALAM MENGATASI KESULITAN SISWA MEMBACA AL-QUR’AN PADA MATA PELAJARAN AL-QUR’AN HADITS DI SEKOLAH MENENGAH ATAS ISLAM NUSANTARA - Anggi Ayu Dwi Narwani; Muchammad Hanief; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This research aims to describe the role of Islamic religious teachers in overcoming the difficulties of students reading the Qur'an about the subjects of the Al-Qur'an Hadith at SMA Islam Nusantara. This research uses a qualitative research approach. Data collection techniques using observation techniques, interview techniques, and documentation techniques. The results of this study indicate how difficult it is for students to read the Koran and the role of Islamic religious teachers in overcoming the difficulties of students reading the Koran on the subject of Al-Qur'an Hadith.